Demands associated with gender in Chilean women with PPD: Family, couple, public health system - Cabello Lopez, Maite (2024)
Introduction: Postpartum depression has been investigated mainly from a biomedical perspective that conceives it as an individual pathology. From the social sciences, some research has highlighted the role of the public health system and support networks, but studies in Chile that consider the experiences of these women are scarce. This research sought to understand these experiences from a gender perspective that considers the social construction of roles and expectations. Methodological framework: A qualitative approach was adopted from grounded theory. The sample was made up of 5 mothers residing in Chile with a diagnosis of postpartum depression. Five semi-structured interviews were conducted, which were analyzed from Grounded Theory. The research was approved by the ethics committee of the Faculty of Psychology of the Diego Portales University. Results: The interviewees point out that the family and the couple can operate as support networks to the extent that they accommodate the mother's needs. Otherwise, when the family and the couple demand the socially expected role for mothers, they were perceived as causing postpartum depression. It was also found that the public health system does not represent a negative influence for these women.